2020
DOI: 10.47947/ijnls.736452
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical use of Stachys L. (Lamiaceae) taxa in Turkey

Abstract: The purpose of this study was to determine the ethnobotanical features of taxa belonging to the genus Stachys L. in Turkish Flora. Their vernacular names and local usages patterns have been determined. To determine the ethnobotanical uses of Stachys L. taxa; ethnobotanical studies made in Turkey have examined. Also, the field study carried out in different regions in Turkey. The ethnobotanical use of 38 Stachys L. taxa (29 species) has been identified in Turkey. The first 2 species that are used most: S. lavan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Son yıllarda yapılan etnobotanik çalıĢmalara baktığımızda tıbbi ve gıda baĢta olmak üzere derleme çalıĢmalarda yoğunluktadır [46][47][48][49][50][51][52][53][54]. Kullanım değeri (KD) hesaplaması [20] son yıllarda yapılan etnobotanik çalıĢmada kullanılmıĢtır [55][56][57][58]…”
Section: Materyal Ve Metotunclassified
“…Son yıllarda yapılan etnobotanik çalıĢmalara baktığımızda tıbbi ve gıda baĢta olmak üzere derleme çalıĢmalarda yoğunluktadır [46][47][48][49][50][51][52][53][54]. Kullanım değeri (KD) hesaplaması [20] son yıllarda yapılan etnobotanik çalıĢmada kullanılmıĢtır [55][56][57][58]…”
Section: Materyal Ve Metotunclassified
“…In Turkey, the genus is represented by 92 species (118 taxa), 53.3% of which are endemic (Güner et al, 2021). These species commonly known as 'mountain tea' are used in many traditional medicines as anti-spasmodic, antimicrobial agent, and herbal tea in order to alleviate asthma problems, to decrease the symptoms of earaches, and to stop the growth of genital tumors and a malignant ulcer (Baytop, 1999;Ebrahimabadi et al, 2010;Sarikurkçu et al, 2016;Satıl & Açar, 2020;Tomou et al, 2020). Many studies conducted on these species have confirmed remarkable anti-inflammatory, antioxidant, antimicrobial, anxiolytic, hypotensive, hyaluronidase, anti-Helicobacter pylori, and anti-nephritic activities (Shang et al, 2010;Tundis et al, 2014;Kocak et al;Satıl & Açar, 2020;Tomou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These species commonly known as 'mountain tea' are used in many traditional medicines as anti-spasmodic, antimicrobial agent, and herbal tea in order to alleviate asthma problems, to decrease the symptoms of earaches, and to stop the growth of genital tumors and a malignant ulcer (Baytop, 1999;Ebrahimabadi et al, 2010;Sarikurkçu et al, 2016;Satıl & Açar, 2020;Tomou et al, 2020). Many studies conducted on these species have confirmed remarkable anti-inflammatory, antioxidant, antimicrobial, anxiolytic, hypotensive, hyaluronidase, anti-Helicobacter pylori, and anti-nephritic activities (Shang et al, 2010;Tundis et al, 2014;Kocak et al;Satıl & Açar, 2020;Tomou et al, 2020). From the chemical point of view, Stachys species were discovered rich in different types of secondary metabolites such as iridoids, di-and triterpenes, alkaloids, phenylethanoid glycosides, flavonoids, phenolic acids, and essential oil (Ahmad et al, 2008;Bahadori et al, 2020;Demirci et al, 2016;Kartsev et al, 1994;Kaya et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plant products include raw or processed plant parts such as roots, stems, leaves, flowers, and seeds [1]. Many Asian, African, and Pacific people utilize traditional medicine as primary health care [2][3][4][5]. In Thailand, particular in rural areas, where access to medical treatments with a Western approach may be expensive or simply not available.…”
Section: Introductionmentioning
confidence: 99%